1999
DOI: 10.1107/s0907444998014589
|View full text |Cite
|
Sign up to set email alerts
|

An accurate numerical model for calculating the equilibration rate of a hanging-drop experiment

Abstract: A numerical model of the equilibration of a hanging-drop experiment has been developed and tested. To obtain accurate calculations with a given precipitant, the vapor pressure of water over water/precipitant solutions must be known for various concentrations of the precipitant. The calculations of the model are in excellent agreement with all available experimental data on hanging-drop equilibration when the necessary vapor pressures are known (ammonium sulfate and sodium chloride). By varying each of the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
4
12
0
Order By: Relevance
“…All of these, save possibly the last, are experimentally optimized (solution composition) or controllable parameters. Diller & Hol (1999) developed a numerical model for the vapor diffusion process, the results of which are in close agreement with the available experimental data to that time. The model showed that there was an approximately linear dependence of the equilibration time with the droplet to reservoir distance and upon the initial droplet size.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…All of these, save possibly the last, are experimentally optimized (solution composition) or controllable parameters. Diller & Hol (1999) developed a numerical model for the vapor diffusion process, the results of which are in close agreement with the available experimental data to that time. The model showed that there was an approximately linear dependence of the equilibration time with the droplet to reservoir distance and upon the initial droplet size.…”
Section: Introductionsupporting
confidence: 71%
“…Note that the equilibration rates at best are only approximately double for an order of magnitude change in the volume ratio. From the model of Diller & Hol (1999), a 10 fold increase in droplet volume results in an approximately 5 fold increase in the equilibration time. B decreasing the reservoir volume we effectively move it further from the droplet, which again would increase the equilibration time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitation of this type of equations is on their restricted applicability, which is confined to the set of conditions at which the empirical parameters were determined. In a different approach, numerical methods were employed to describe the equilibration of hanging drop experiments reported in literature; the software program “Drop” was presented as being based on the FM and SM but with fewer geometric assumptions, and was reported to adequately describe the experimental data [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nanodrop crystallization trials reduce the required protein sample size, allowing for more complete exploration of crystallization parameter space, as well as for improved rates of drop equilibration (18) and successful crystal production. Faster crystal formation permits faster feedback, and, perhaps more surprisingly, can lead to improved crystal quality due to decreased decomposition and degradation.…”
Section: Expressmentioning
confidence: 99%